Diseño de capacidad de un embalse de agua con fines de riego, en la cuenca de la quebrada La Cucula. - Vivanco Encalada, Edwin Fabricio (2018)
This project is located in the neighborhood of Valle Hermoso, borough Buena Vista which belongs to the canton Chaguarpamba in the province of Loja; the main objective of this project is solving the irrigation problem that affects it in times of water deficit; For this, the design of the capacity of a reservoir is proposed; since when thoroughly review the climatic behavior of the study area, there are two distinct stages: time of plenty and times of water scarcity, For this reason, farmers in the area are forced to carry out agricultural work when there are rains, while in times of scarcity they do not sow, or the yield obtained turns out to be much lower than expected. The proposal raises in the first instance the existence of water for irrigation of constant way, by means of the proposal of a zone of irrigation in which the production is continuous. For this, it was necessary to start from the study of the supply of water resources, it began with the selection of the point of interest in which the project will be developed, the point of interest must be located in a tributary of water, and in an area topographic that allows to dam the hydric resource, once defined, the delimitation of the basin has been made and the morphometric parameters of the same have been obtained; it must be taken into account that the entire project was developed through the use of GIS software; meteorological stations surrounding the study area were selected, in this case: Catacocha, Celica, and Zaruma; by rainfall data base recorded in those stations it proceeded with filling missing data, and culminating in the generation of flows by different methods; one of them was selected, by comparing them and the monthly assessments made at the point of interest. The process was continued by calculating the demand for water, and ended with the proposal of an irrigation area with profitable crops and there to be produced; To calculate the water demand, the crop coefficient (Kc) was calculated; The Eto was obtained through the meteorological stations and with the temperature database. by means of it, crop evapotranspiration (Etc) was calculated; With this data and the effective precipitation of the irrigation area, the water needs of the aforementioned area were calculated. Finally by the methods of the algorithm of succession of peaks and method of the curve of mass in reverse, the useful volume of the reservoir was obtained; Then the water balance was calculated in the same and after the calculation of dead volume and minimum volume of operation, the total volume of the reservoir was obtained, the height of the wall, and finally the curves, height-volume, and height-area; which are characteristic curves of a reservoir; This process from start to finish was done through the use of GIS, and methods identified in the project methodology.